Hubungan Perilaku Merokok Terhadap Motivasi Belajar Siswa Di MAN 6 Aceh Besar - Urip Pratama; Yusrika Yusrika; Yadi Putra (Calory Journal Medical Laboratory Journal, 2024)
Motivation to learn is very important for achieving performance or learning achievement. Learning motivation can be seen from students' learning achievements and cognitive aspects. Awareness of student learning motivation can be seen from the lifestyle of each individual student. The aim of this research is to determine the relationship between smoking behavior and student learning motivation at MAN 6 Aceh Besar. This research uses a quantitative analytical design using a cross sectional study method. The population in this study was 128 male students. The sampling technique used is Proportional Random Sampling. The sample used in this research used the Slovin formula. The number of samples taken in this research was 56 respondents. The instrument used in this research used a questionnaire sheet. The results of the research are that there is a relationship between smoking behavior and students' learning motivation at MAN 6 Aceh Besar with a value of p = 0.000. There is a relationship between smoking behavior and students' learning motivation in terms of peer influence at MAN 6 Aceh Besar with a value of p = 0.027. There is no relationship between smoking behavior. Regarding student learning motivation from a lifestyle perspective at MAN 6 Aceh Besar with a value of p = 0.819 and there is a relationship between smoking behavior and student learning motivation from an environmental perspective at MAN 6 Aceh Besar with a value of p = 0.004. Researchers suggest that schools provide regular outreach about the dangers of smoking on students' learning motivation.